2010
DOI: 10.1111/j.1365-2648.2009.05229.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy beliefs predict collaborative practice among intensive care unit nurses

Abstract: Background. Recent empirical studies in the field of work and organizational psychology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
1
21
0
8
Order By: Relevance
“…Este resultado es contradictorio con el de otras investigaciones que relacionan positivamente el engagement con la recuperación (Le Blanc et al, 2010;Nerstad et al, 2010;Sonnentag, 2003). Dada esta contradicción, una futura línea de profundización podría ir en la dirección de estudiar la calidad de las actividades realizadas en este tiempo libre, ya que esta diferencia de disponibilidad temporal podría verse compensada por la realización de actividades que tuvieran mayor poder compensador o de recuperación.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Este resultado es contradictorio con el de otras investigaciones que relacionan positivamente el engagement con la recuperación (Le Blanc et al, 2010;Nerstad et al, 2010;Sonnentag, 2003). Dada esta contradicción, una futura línea de profundización podría ir en la dirección de estudiar la calidad de las actividades realizadas en este tiempo libre, ya que esta diferencia de disponibilidad temporal podría verse compensada por la realización de actividades que tuvieran mayor poder compensador o de recuperación.…”
Section: Discussionunclassified
“…Igualmente, se ha visto que los alumnos con actitudes positivas hacia sus tareas cuentan con mayores y mejores habilidades emocionales, lo que potencia el factor amortiguador del estrés académico y mejora el rendimiento por parte de los estudiantes (Extremera y Durán, 2007;Extremera y Fernández-Berrocal, 2006). En este sentido parece que el engagement se relaciona con la recuperación tanto física, como mental y emocional, del cansancio de la jornada anterior (Le Blanc, Schaufeli, Salanova, Llorens y Nap, 2010;Nerstad, Richardsen y Martinussen, 2010;Sonnentag, 2003).…”
Section: Introductionunclassified
“…For example, Le Blanc, Schaufeli, Salanova, Llorens, and Nap (2010) conducted a longitudinal study in two waves on 372 nurses working in 29 different European intensive care units to show that efficacy beliefs predict collaborative practice through team commitment, which are reciprocally related to each other. Furthermore, research suggests an upward gain-spiral in which efficacy beliefs (both individual and collective) reciprocally influence activity engagement (work and task engagement) indirectly through their impact on positive affect (enthusiasm, satisfaction, and comfort) over time.…”
Section: Positive and Transformational Leadershipmentioning
confidence: 99%
“…A meta-analysis found self-efficacy belief responsible for 28% gain in worker performance (Stajkovic and Luthans, 1998), although other more distal personal variables, such as experience and emotional stability, were also important (Judge et al, 2007). Individual self-efficacy beliefs predicted collaborative practice (Le Blanc et al, 2010). At the team level considerable evidence from organisational psychology studies of business or manufacturing teams showed those with higher collective efficacy performed to higher standards (Bandura, 1997: Gully et al, 2002: Hoyt et al, 2003.…”
Section: Personal Factorsmentioning
confidence: 99%